The Influence of Human Resource Development Strategy, Personnel Competence and Work Motivation On Performance of The Personnel of 242 Radar Unit Tanjung Warari - Qatamsi, Mochammad Jihad Fisabilillah; Arifin, Antoni Ludfi (Dinasti International Journal of Management Science, 2025)
This research aims to the influence of human resource development strategy, personnel competence, and work motivation on the performance of Radar Unit 242 Tanjung Warari. This research uses a quantitative approach, survey methods and path analysis. The population is 90 of personnel. With a simple random sampling technique, 70 respondents were obtained. Data were analyzed using Excel and SPSS. The research results show that: human resource development strategy has a direct positive and significant effect on work motivation of 0,432; personnel competence has a direct positive and significant effect on work motivation of 0,450; human resource development strategy has a direct positive and significant effect on performance of 0,428; personnel competence has a direct positive and significant effect on performance of 0,262; work motivation has a direct positive and significant effect on performance of 0,234. Implications, to increase the performance of Radar Unit 242 Tanjung Warari to improve the human resource development strategy, personnel competence, and work motivation.